Desain Prototype Sistem Informasi Akuntansi Kas Keluar pada Usaha Desain Baliho Aditya Creative - Falih Adya Wicaksono; Ramliadi; Igas Rio Simpado; Raja Sabaruddin (Jurnal Sistem Informasi Akuntansi, 2025)
This study addresses cash outflow management challenges faced by Aditya Creative, a small-medium enterprise (SME) in banner design services. Manual recording practices caused unclear expenditure tracking, transaction evidence disorganization, and operational inefficiencies. To resolve these issues, we designed a web-based cash outflow accounting system prototype using the Waterfall SDLC methodology (focused on requirement analysis and design stages). Data were collected through field observation, SME owner interviews, and literature review on system modeling. The prototype was developed with UML diagrams (Use Case, Activity, Sequence) and Figma interface designs, featuring core functionalities: Real-time cash outflow recording, expenditure monitoring dashboard, customizable report generation, data filtering/editing/deletion, digital proof-of-payment storage. Results demonstrate a user-centric solution that streamlines financial operations through automated recording and reporting. The prototype eliminates manual bookkeeping errors while providing actionable insights via visual expenditure analytics. This design serves as a foundational framework for future implementation of a fully functional system, potentially expandable to cash inflow management for comprehensive SME cash flow optimization.